Evaluation of antimicrobial activity and phytochemical constituents of Saraca asoca stem bark. - Naidu, Lagudu M (Open Access Journal of Medicinal and Aromatic Plants, 2018)
The aim of the present study is an attempt to explore the antimicrobial activity of hexane, chloroform, methanol and aqueous extracts of stem bark of Saraca asoca by agar well diffusion method. The microbial strains used in the study are Bacillus subtilis, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Micrococcus luteus, Pseudomonas aeruginosa, Proteus vulgaris, Staphylococcus aureus, Streptococcus pneumoniae, Aspergillus niger, Candida albicans and Saccharomyces cerevisiae. The methanolic extract of S. asoca stem bark showed the strongest antimicrobial activity compared to the all other extracts. The preliminary phytochemical screening of S. asoca stem bark revealed the presence of phytoconstituents such as carbohydrates, cardiacglycosides, terpenoids, alkaloids, flavonoids, phenols, tannins, amino acids, quinines and saponins. Methanol, aqueous and chloroform extracts shown MIC lower than125 Âµg/ml, demonstrating that the stem bark of S. asoca has strong antimicrobial activity. The high degree of antimicrobial activity seems to confirm the folk therapy of infections support the folkloric usage of the studied plant, S. asoca as a medicine. Hence, it is necessary to explore the maximum potential of the plant in medicinal field and pharmaceutical sciences for further application.